Identification and exploration of pharmacological pyroptosis-related biomarkers of ulcerative colitis - Chen, Kaiwei; Shang, Shipeng; Yu, Shengnan; Cui, Luwen; Li, Shangyong; He, Ningning (Frontiers in Immunology, 2022)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease with unclear etiology, but disruption of the intestinal barrier caused by abnormal death of intestinal epithelial cells (ICEs) and the subsequent inflammatory response may be central to UC. Pyroptosis is a form of programmed inflammatory cell death, and also a significant mode of death for ICEs. However, the relationship between pyroptosis and UC remains to be explored and the molecular mechanisms are still poorly understood. In this study, the hub genes and key immune cells related to pyroptosis of UC were identified by bioinformatics analysis. 10 hub genes related pyroptosis were determined by identifying common genes of database mining, WGCNA analysis and differentially expressed genes (DEGs) identified by gene expression profiles obtained from the GEO database. Biomarkers were screened according to gene significance (GS) & Module Membership (MM). CIBERSORT explored the immune infiltration landscape. In addition, we further investigated the regulatory effects of the mild UC therapeutic drugs on the hub gene in the treatment of UC. The results indicated the hub genes related to pyroptosis were closely related to the progression of UC and response of therapeutic drugs. By analyzing CD45+ colonic lamina propria single-cell RNA (scRNA) sequencing data from UC patients, the immune cells most related to pyroptosis were evaluated and the expression pattern of hub genes in immune cells was explored. Finally, it was identified that macrophages were most related to the occurrence of pyroptosis. Four different macrophage clusters were identified based on hub gene expression, pseudotime analysis and enrichment analysis. In addition, the DSS-induced colitis mice was used to study the expression of pyrosis related hub gene and the effect of 5-ASA on its expression. In summary, our study identified IL1B is the key pyroptosis-related biomarker in UC, providing a new perspective on the pathogenesis and therapeutic options for UC. The crosstalk between macrophages pyroptosis and ICEs pyroptosis may play an important role in UC, which deserves further exploration.